Measuring the success of cross-tenure collaborative weed management: insights codeveloped with practitioners. (23rd December 2022) - Graham, Sonia; Wyllie, Megan; Wilkerson, Mel; Williams, Michael; Sharp, Angela; Cherry, Hillary; Martin, Paul; Campbell, Rebecca; Hawkes, Gina
Abstract: There is limited documentation of cross-tenure collaborative weed management programs, and no consistent set of metrics for evaluating their performance. In this study, 12 weed management practitioners in southeast Australia participated in a qualitative social research project to discuss and document examples of cross-tenure collaborative weed management and critically reflect on whether existing metrics are suitable for evaluating the performance of their programs. Analysis of focus group discussions, project documentation, subsequent reflections, and review of the literature reveal that weed management practitioners, in Australia and elsewhere, mostly rely on metrics that measure weed management inputs, such as herbicides, labor, and costs. Metrics used to evaluate social outcomes focus on benefits for individuals rather than social relationships or achievement of equitable outcomes. Social research on collaborative governance and social science methods more broadly, such as social network analysis and collective narratives, could be used by weed management practitioners to better evaluate and explain social–ecological outcomes over time.